Making History compulsory”: Politically inspired or pedagogically justifiable? (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
While recognising the contested nature of History as a school subject, this article explores the political context and practical implications of making History compulsory until Grade 12. After twenty one years of democracy, South African society lacks social cohesion, a sense of nationhood and is experiencing occurrences of xenophobia. To address these concerns, the Department of Basic Education (DBE) established the History Ministerial Task Team (HMTT) to oversee the implementation of compulsory History in the Further Education and Training (FET) phase. The terms of reference of the task team include: the strengthening of History content; a review of the content in the General Education and Training (GET) band; its implication for teacher education, professional development and textbooks. The campaign to make History compulsory was promoted by the South African Democratic Teachers Union (SADTU) and intensified after the outbreak of xenophobic attacks in 2008. To maintain the academic and professional statu of History teaching, this article attempts to answer the question: what is the purpose of History as a school subject? To respond to this question, Barton and Levstik’s model: “the purposes of History teaching”, is employed as a framework to evaluate the proposal. By conducting a review of the post-apartheid History curriculum with special reference to complex phenomena such as nation-building and xenophobia, this article argues for attention to be given to the improvement of teachers’ pedagogical practice and historical knowledge rather than policy reform which may be destabilising a large segment of the school system. The anticipated HMTT report is alerted against gratuitous political interference and to some practical implications of its work for educational practice.
Keywords: CAPS; Citizenship education; Curriculum; History as compulsory; Nation-building; Third space; Xenophobia